Formaldehyde Test and pH of Julung Julung Fish (Hemiramphus brasilirnsis) Smoke in Traditional Markets Gorontalo City - Masniah H Inombi; Meriyanti Ngabito; Ida Astuti (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2019)
The results of processed julung - julung fish (Hemiramphus sp) immediately in Gorontalo are called sagela. Formaldehyde, better known as formaldehyde, is one of the additives that can be consumed but will be used by people as preservatives for food. The purpose of this study was to determine the formaldehyde content and pH of julung - julung fish as soon as possible in 6 traditional markets in Gorontalo City. This research uses purposive sampling method. Based on the results of research that has been done with qualitative tests using formaldehyde test kits, it is found that formaldehyde is not displayed on 18 samples of julung-julung fish taken from the daily and weekly markets sold in Gorontalo City. The pH value of julung - julung fish which is marketed in Gorontalo City is still included in the criteria agreed below. 7. Place julung - julung fish as soon as possible to be marketed in Gorontalo City which is suitable for consumption and is sold with good quality.